The Philosophy and Science of Predictive Processing 2020
DOI: 10.5040/9781350099784.ch-011
|View full text |Cite
|
Sign up to set email alerts
|

The Phenomenology and Predictive Processing of Time in Depression

Abstract: third-party websites referred to or in this book. All internet addresses given in this book were correct at the time of going to press. The author and publisher regret any inconvenience caused if addresses have changed or sites have ceased to exist, but can accept no responsibility for any such changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Phenomenologists are interested not in the qualia of greenness, but in the structural invariants that are expressed in all phenomenal consciousness, such as intentionality or the temporal structure of cognition and consciousness. We will close this section by describing the eidetic structure of what phenomenologists call time-consciousness ( Husserl, 1917/1991 ; Neemeh and Gallagher, 2020 ). We will hypothesize a way that this eidetic structure may be realized as a neurocomputational structure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Phenomenologists are interested not in the qualia of greenness, but in the structural invariants that are expressed in all phenomenal consciousness, such as intentionality or the temporal structure of cognition and consciousness. We will close this section by describing the eidetic structure of what phenomenologists call time-consciousness ( Husserl, 1917/1991 ; Neemeh and Gallagher, 2020 ). We will hypothesize a way that this eidetic structure may be realized as a neurocomputational structure.…”
Section: Discussionmentioning
confidence: 99%
“…The subjective experience of time has a formal eidetic structure, what Husserl (1917/1991) calls time-consciousness. While we usually imagine time to be a linear arrow, phenomenologists contend that time-consciousness has a far more complicated, looping structure ( Neemeh and Gallagher, 2020 ). Take the perception of a melody.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Predictive processing proponents have repeatedly discussed research positing that emotionally charged mental models lead people to see weapons where there are none (e.g., Fridman et al 2019;Neemeh 2020). One experiment (Wormwood et al 2017) focused on the aftermath of the 2013 Boston Marathon bombing and reported that angry locals tended to judge that people holding neutral objects were armed.…”
Section: Cognizing Created Realitiesmentioning
confidence: 99%
“…Finally, although the basic sense of time is more closely related to individual measure-ments, it can be argued that at least some aspects of the human experience correspond to the inferred posterior durations that integrate multi-modal information with memory (Von Helmholtz 1867/1906, Seth 2015, Neemeh & Gallagher 2020. In particular, studies of the phenomenology of time have suggested a separation that comprises implicit (or lived) and explicit time (Fuchs 2013).…”
Section: Bayesian Approaches To Interval Timingmentioning
confidence: 99%